Analisis Survival Penyakit Jantung Koroner Berulang - Fidya Panorama Damayanti; Arief Wibowo (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
Survival analysis is one of data analysis the result showing certain times had happened. Cox regression analysis is one of the most powerful and commonly used for analyzing survival data since the result of this method showing nearly similar result to parametric model. This study aim is to determine case of recurrent Coronary Heart Disease risk factors, and to know how many survival in day of recurrent Coronary Heart Disease based on the risk factors at RS Islam Surabaya in 2015 – 2016. Measurement in research subjects was conducted in the medical record. This research using observational research approach. Subjects were 63 Coronary Heart Disease inpatients in RS Islam Surabaya. Measurement was conducted to obtain information of examined variables. Independent variables were data sensor status, survival time (measured in day), sex, age, hypertension, hyperlipidemia, and diabetes mellitus. This analysis showing the occurrence time average of recurrent CHDs in Coronary Heart Disease patients in general is 614 days. Rate of reccurence had similar risks for all age groups, gender, hypertension, hyperlipidemia, and diabetes mellitus. CHD patients with hypertension status have risk of 9.291 times greater than no hypertension status. This research can be used by RS Islam Surabaya to gave Communication, Information, and Education to the patient and their relatives especially for patient with hypertension status to have continuous check-up in order not to get another recurrent event of CHD in the near future.